Prominence of Cu in a plasmonic Cu-Ag alloy decorated SiO2@S-doped C3N4 core-shell nanostructured photocatalyst towards enhanced visible light activity - Babu, Pradeepta; Dash, Soumya Ranjan; Behera, Arjun; Vijayaraghavan, T.; Ashok, Anuradha; Parida, Kulamani (Nanoscale Advances, 2021)
A series of Cu-Ag bimetal alloys decorated on SiO2 and the fabrication of few-layer S-doped graphitic carbon nitride (SC) warped over it to form a core-shell nanostructured morphology have been demonstrated and well characterized through various physiochemical techniques. HRTEM data confirmed the formation of a compact nanojunction between the SiO2 and SC, where Cu-Ag is embedded uniformly with an average particle size of 1.3 nm. The Ag : Cu (1 : 3) between SiO2 and SC produces 1730 mu mol h(-1) g(-1) of H-2 under visible light illumination. Moreover, 6.2-fold current enhancement in the case of Ag : Cu (1 : 3) as compared to the Ag-loaded core-shell nanostructured photocatalyst indicates higher electron-hole-pair separation. The excellent activity was due to the synergistic alloying and plasmonic effect of Ag and Cu. DFT studies reveal that the Cu atom in the Cu-Ag bimetal alloy plays a pivotal role in the generation of H-2, and the reaction proceeds via a 4-membered transition state. The mechanistic insight proceeds from the generation of hot electrons due to the LSPR effect and their transfer to the SC layer via a compact nanojunction.